(untitled) (MULTIDISCIPLINARY JOURNAL: FUNDAMENTAL RESEARCH SCIENTIFIC JOURNAL, 2025)
Transboundary water resources play a critical role in supporting ecological systems, socio-economic development, and regional cooperation. However, managing these shared water bodies presents significant ecological security challenges and hydro-economic conflicts due to differing national interests, pollution, and over-extraction. This paper examines the importance of sustainable and cooperative management approaches to ensure equitable water distribution, maintain ecosystem health, and prevent conflicts. It highlights the need for integrated policies, legal frameworks, and international collaboration to address ecological risks and optimize hydroeconomic benefits in transboundary basins.